(3JSOjO GdbhS aj eNJUQ GdaQOhS dCHi efUhQ GdOjdejs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3CHh efUhQ GdOjdejs
(3ChdgG (B:s
(3jHJOF HMQa GdHGA s
(3BNQgG (B:s
(3hjfJgi HBNQ MQa GdaGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B68 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1684s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH Yf jfi LGeY (B((3MOjK (B2099) s
Keywords: (3GdMOjK h GdeUWdMs